Review of the leafhopper genus Singapora Mahmood (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) - Cao, Yanghui; Yang, Meixia; Zhang, Yalin (Zootaxa, 2014)
General characteristics of Singapora Dworakowska and a key to known species of the genus are provided. Six new species, Singapora candela, S. excedens, S. falcata, S. longiantrosa, S. triacantha and S. yingjiangica spp. nov. are described and illustrated, with two new records, S. shivae Dworakowska from China and S. bannaensis Song & Li from Thailand.